Correction: Kujawski et al. Autonomic and Cognitive Function Response to Normobaric Hyperoxia Exposure in Healthy Subjects. Preliminary Study. Medicina 2020, 56, 172 - Sławomir Kujawski; Joanna Słomko; Karl J. Morten; Modra Murovska; Katarzyna Buszko; Julia L. Newton; Paweł Zalewski (Medicina, 2024)
There was an error in the original publication [...]